A case study of new approaches to address health inequalities: Due North five years on. Issue 1 (27th December 2019) - Johnstone, Paul W
Abstract: Introduction: When local councils took on responsibility for public health in England in 2013, leaders from across the north of England met to consider the scale of the challenge. As a result, Public Health England commissioned the Due North Report which outlined new approaches in tackling health inequalities. This second paper outlines what has been learnt in five years as a case study. This includes influencing devolution deals and new elected city mayors, planning for economic growth in deprived areas and developing community asset-based approaches. The paper outlines a new framework for place-based planning to reduce health inequalities. Sources of data: Data was gathered from annual reports from north of England directors of public health, Office for National Statistics, Public Health England's fingertips database and regional and national publications and strategies such as the Northern Powerhouse. Areas of agreement: Devolution to English cities and councils as 'places' is a new opportunity to address local needs and inequalities. Due North has supported a new public health narrative which locates health action in the most fundamental determinants—how local economies are planned, jobs created and power is to be transferred to communities and connects reducing years of premature ill health to increased economic productivity. Community asset approaches to empower local leaders and entrepreneurs can be effective ways to achieve change. Areas of controversy: The north–south divide in health is not closing and may be worsening. Different ways of working between local government, health and business sectors can inhibit in working together and with communities. Growing points: Place-based working with devolved powers can help move away from top down and silo working, empower local government and support communities. Linking policies on health inequalities to economic planning can address upstream determinants such as poverty, homelessness and unsafe environments. Areas timely for developing research: More research is needed on; (i) addressing inequalities at scale for interventions to influence community-led change and prosperity in deprived areas, and (ii) the impact of devolution policy on population health particularly for deprived areas and marginalised group. Discussion and conclusions: Commissioning high profile reports like Due North is influential in supporting new approaches in reducing inequality of health through local government, elected mayors; and working with deprived communities. This second paper describes progress and lessons.